Decadal variability of the Turner Angle in the Mediterranean Sea and its implications for double diffusion. (August 2016) - Meccia, Virna L.; Simoncelli, Simona; Sparnocchia, Stefania
Abstract: The physical reanalysis component of the Mediterranean Forecasting System is used to construct a high-resolution three-dimensional atlas of the Turner Angle. An assessment of the model quality shows a maximum degree of agreement with observations in the water column between 150 and 1000 m depth. The mean state of the favourable conditions for double diffusion processes is evaluated and the recent decadal variability is studied in terms of changes in the water mass properties. The results show that approximately 50% of the Mediterranean Sea is favourable to double diffusion processes, from which around 47% is associated with salt fingering. The Tyrrhenian, Ionian and southwestern Mediterranean are the most vulnerable basins to salt fingering, and the strongest processes can occur in the Tyrrhenian deep waters. Diffusive convection is most likely to occur in the Ionian, Aegean and eastern Mediterranean at vertical levels deeper than 1000 m. The observed gradual warming and salinification of the Mediterranean after 1997 decreased and increased the possibilities of the occurrence of salt fingers and double diffusive convections, respectively. The climatological atlas that is presented in this paper provides a three-dimensional picture of the regions that are either doubly stable or favourable to double diffusion instability and allows for the characterization of the diffusive properties of the water masses. Highlights: An atlas of the Turner Angle for the Mediterranean Sea is presented. Approximately one half of the Mediterranean Sea is favourable for double diffusion. The strongest salt fingering can occur in the Tyrrhenian deep waters. A gradual warming and salinification of the Mediterranean Sea is observed. The possibility of developing salt fingering decreased after 1997.